Editorial – 2020 - Thematic Issue Research Methodology in Mathematics Education: directions and perspectives - de Oliveira, Gerson Pastre; Almouloud, Saddo Ag; Manrique, Ana Lucia (Educação Matemática Pesquisa: Revista do Programa de Estudos Pós-Graduados em Educação Matemática, 2021)
Editorial in English